Study of effect of ethanol on antioxidant - vitamin A and C in rat liver - Singh, AR; Kumar, Sushil; Takhelmayum, Roshan; Sihna, JN (Journal of College of Medical Sciences-Nepal, 2010)
Objective: To see the effect of consumption of locally distilled alcohol (country liquor) continuously for few months on hepatic vitamin A and C status in albino rats. Materials and methods: The study was conducted in 36 male wistar strain albino rats for 3-4 months old consisting six groups of six animals each. Results: The first observation was weight gain among the series of alcoholic animals when compared to the control and alcoholic fed animals supplemented with vitamin A and C, p-value by T-test between the mean values of the initial weight and final weight was < 0.01 (0.006), significant. Conclusion: It was found that the major effect on hepatic vitamin A and C contents were observed more distinctly in mitochondrial fractions when compared with the rest fractions. Supplementation of vitamins helped to protect loss of the vitamins which delayed the aging process at age 9-10 months in our study. Key words: Albino rats; alcoholic; hepatic; vitamin A DOI: 10.3126/jcmsn.v6i1.3599 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 29-34